Pengaruh Karakteristik Komite Audit Terhadap Financial Distress Dengan Penerapan Sistem Whistleblowing Sebagai Variabel Moderasi - Vicky Febriana; Yulius Jogi Christiawan (Business Accounting Review, 2020)
Every company has a different financial condition. Some are in a safe zone and some are in difficult zone. This study aimed to examined the implementation of the whistleblowing system can strengthen the relationship between the characteristics of audit committee on financial distress. The study was conducted on 90 companies from manufacturing sector which were listed in the Indonesia Stock Exchange in the period of 2015 to 2019. This study measured financial distress by using the Altman Z-Score model and dummy to measures the implementation of whistleblowing system. The size of audit committee, Independency of audit committee, and frequency of audit committee meetings using the company’s financial report. This test conducted by using Weighted Least Square method, but this study did not succeed in proving the implementation of the whistleblowing system strengthen the relationship between the independence of audit committee and frequency of audit committee meetings on financial distress.